Menggali Kearifan Lokal Melalui Tradisi Melemang 10 Muharram: Warisan Budaya Islam di Desa Karang Raja - Putri Sidahtilla Umma; Hudaidah Hudaidah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Melemang tradition is a form of local wisdom of the people of Karang Raja Village, Muara Enim, which is held every 10th of Muharram. This tradition not only has cultural values, but also has social and religious values such as gotong royong, caring, and sharing. However, in the midst of modernisation and the declining interest of the younger generation in traditional culture, the question arises of how best to keep the Melemang tradition from disappearing. The purpose of this research is to study ways to preserve the Melemang culture and develop methods that can be used to introduce the culture to the general public. This research uses a descriptive-analytical approach and a qualitative approach through, interviews, and literature research. The results showed that the involvement of the younger generation is necessary to preserve the Melemang tradition. It is hoped that this effort will strengthen cultural identity and introduce the melemang tradition to the general public.